Associação entre o potencial evocado auditivo de longa latência e os índices lineares da variabilidade da frequência cardíaca em repouso - Marcomini, Renata Sperancin [UNESP] (2015)
Introduction: The literature has investigated the relationship between auditory stimulation and the cardiovascular system. Both the auditory processing and cardiovascular modulation are regulated by the central nervous system. Auditory long latency response is bioelectric activity of the thalamus and cortex and provides precise information regarding auditory information processing time, in milliseconds, while the heart rate variability (HRV) is a noninvasive technique that analysis the autonomic nervous system modulation. Objective: To investigate the association between the components of the long latency auditory evoked potential (ALR) and cardiac autonomic regulation. Method: The study was conducted on 23 healthy male subjects between 20 and 43 years old. HRV was recorded at rest for 10 minutes through the heart rate monitor (Polar RS800CX). Subsequently, the following components were analyzed ALR: N1 (N100), P2 (P200), N2 (N200) and P3 (P300). The Pearson correlation was applied for parametric distributions and Spearman correlation test for nonparametric distributions was applied to analyze and assess the correlation between the components of ALRs and HRV indices. Results: All indices of HRV correlated moderately with statistical significance, it changed according to the ALR component. The indices in the time domain (SDNN, average heart rate, rMSSD and pNN50) correlated between the amplitude of the N2 component in afferent left on frequency. In relation to the frequency domain, the LF (ms2) index correlated between the amplitude of the N1 component in the afferent left on frequency, right afferent N2 and P3 in the frequency afferent left in duration, and the interamplitude the N2-P3 in afferent left ear in duration; LF (nu) index between the latency of P2 and N2 in afferent left on duration and latency of N2 in afferent left on frequency; HF (ms2) index correlated between the amplitude of the N2 component in the frequency afferent to...